Coronary heart disease risk markers in users of low-dose oral contraceptives - Godsland, I F; Crook, D; Wynn, V (Journal of reproductive medicine, 1991)
Seven combination oral contraceptives (OCs) were studied for their effects on glucose, insulin, triglyceride and lipoprotein concentrations. Subjects included 925 women using fixed-dose (monophasic) or variable-dose (triphasic) formulations and 418 premenopausal women not using OCs. The monophasics contained 150 or 250 micrograms of levonorgestrel, 500 or 1,000 micrograms of norethindrone or 150 micrograms of desogestrel as the progestin. Triphasic progestin doses were 50-125 micrograms of levonorgestrel or 500-1,000 micrograms of norethindrone. All the formulations increased the fasting serum triglycerides. No changes were seen in serum total cholesterol. The effects on serum lipoproteins depended on the progestin type and dose. Monophasics containing 500 micrograms of norethindrone or 150 micrograms of desogestrel lowered low density lipoprotein (LDL) cholesterol and increased high density lipoprotein (HDL) cholesterol. Monophasics containing levonorgestrel reduced HDL cholesterol. The triphasics did not affect LDL or HDL cholesterol but altered the balance of HDL subfractions. All the formulations caused a deterioration in glucose tolerance and insulin resistance and increased pancreatic insulin secretion. The greatest effects were seen with formulations containing levonorgestrel. The study showed that a reduction in the progestin dose and use of novel progestins can reduce the potentially adverse effects of OCs on metabolic risk markers for coronary heart disease.